Link Between Synovial and Myocardial Inflammation: Conceptual Framework to Explain the Pathogenesis of Heart Failure with Preserved Ejection Fraction in Patients with Systemic Rheumatic Diseases - Milton Packer (Radcliffe Medical Media, 2020)
Patients with a broad range of systemic rheumatic diseases are at increased risk of heart failure (HF), an event that is not related to traditional cardiovascular risk factors or underlying ischaemic heart disease. The magnitude of risk is linked to the severity of arthritic activity, and HF is typically accompanied by a preserved ejection fraction. Subclinical evidence for myocardial fibrosis, microcirculatory dysfunction and elevated cardiac filling pressures is present in a large proportion of patients with rheumatic diseases, particularly those with meaningful systemic inflammation. Drugs that act to attenuate pro-inflammatory pathways (methotrexate and antagonists of tumour necrosis factor and interleukin-1) may ameliorate myocardial inflammation and cardiac structural abnormalities and reduce the risk of HF events.